2015
DOI: 10.4238/2015.february.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Expression and genomic integration of transgenes after Agrobacterium-mediated transformation of mature barley embryos

Abstract: ABSTRACT. Mature embryos in tissue cultures are advantageous because of their abundance and rapid germination, which reduces genomic instability problems. In this study, 2-day-old isolated mature barley embryos were infected with 2 Agrobacterium hypervirulent strains (AGL1 and EHA105), followed by a 3-day period of cocultivation in the presence of L-cystein amino acid. Chimeric expression of the b-glucuronidase gene (gusA) directed by a viral promoter of strawberry vein banding virus was observed in coleoptile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Our results showed that transgene integration occurred unevenly among the chromosomes of A, B and D genomes, with integration sites at different locations along individual chromosomes, there was only a slight tendency toward localization to distal regions. Similar to our findings, T-DNA insertion sites generated under non-selective conditions are not biased to any particular genomic region by Agrobacterium-mediated transformation (Kim and Gelvin 2007;Uçarlı et al 2015) and direct microinjection of foreign DNA is randomly integrated into chromosomes in transgenic animals (Yan et al 2013). Furthermore, transformation frequency was demonstrated to be higher for cells in the M or G2 phase compared to the S phase of the cell cycle in one study (Iida et al 1991) but in other later studies it was shown to be higher in the S and G2 (Arias et al 2006) or S and M (Villemont et al 1997) phase of the cell cycle.…”
Section: Transgenic Ressupporting
confidence: 91%
“…Our results showed that transgene integration occurred unevenly among the chromosomes of A, B and D genomes, with integration sites at different locations along individual chromosomes, there was only a slight tendency toward localization to distal regions. Similar to our findings, T-DNA insertion sites generated under non-selective conditions are not biased to any particular genomic region by Agrobacterium-mediated transformation (Kim and Gelvin 2007;Uçarlı et al 2015) and direct microinjection of foreign DNA is randomly integrated into chromosomes in transgenic animals (Yan et al 2013). Furthermore, transformation frequency was demonstrated to be higher for cells in the M or G2 phase compared to the S phase of the cell cycle in one study (Iida et al 1991) but in other later studies it was shown to be higher in the S and G2 (Arias et al 2006) or S and M (Villemont et al 1997) phase of the cell cycle.…”
Section: Transgenic Ressupporting
confidence: 91%
“…Consistently, the transcript level of MePDS in MePDS -VIGS plants were 37.9%–53.1% of that in the mock, with an obvious albino phenotype and a 58%–76.5% level of chlorophyll. Compared with GV3101, Agrobacterium AGL-1 showed better effects in the VIGS system (Table 2), which might have been due to the specific hypervirulence of AGL-1 [46]. AGL-1 is derived from pTiBo542, which has a high induction of the vir gene [47], which is necessary for T-DNA transfer [48].…”
Section: Discussionmentioning
confidence: 99%